Memori dan Trauma dalam Hubungan Internasional: Dukungan Austria Terhadap Israel dalam Melawan Aksi Boikot, Divestasi, dan Sanksi (BDS) - Adilah Hasna Khairunisa; Mohamad Rosyidin; Muhammad Faizal Alfian (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The Boycott, Divestment, and Sanctions (BDS) campaign against Israel continues to this day, with many countries and international organizations supporting the action. Nonetheless, there is a country that prohibits such behavior and expresses its support for Israel in its fight against what is considered anti-Semitism. Austria is the name of that so-called country. The purpose of this research is to determine why Austria decided to support Israel in its fight against BDS using the Memory, Trauma and World Politics theory by Duncan Bell. The researcher gathered various supporting data from books, websites, international news, and official statements from the Austrian government using the literature review technique. This is an explanatory research that aims to discover the reasons why Austria supports Israel in its fight against BDS, which is related to the country's past history and existing trauma. The findings of this study show that there are memories and traumatic events in the past in the form of anti-Semitism against the Jewish community in Austria, which caused a sense of responsibility and solidarity from Austria towards Israel as an existing Jewish state. Austria's sense of responsibility and solidarity eventually encouraged the establishment of current policy.